Reframing in Organisational Renewal Processes - Krzakiewicz, Kazimierz; Cyfert, Szymon (Reframing w procesie odnowy organizacji, 2010)
The main purpose of this article is to describe the reframing concept in the process of organisational renewal. The article first sets out to present general assumptions in reframing and then goes on to characterise the three stages in the reframing process: reaching mobilisation, defining a vision of changes, and building a system of strategic goals, actions and indicators.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 48-54
Keywords: strategic renewal of organisations